2021
DOI: 10.1021/jacs.1c02272
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Heterogeneous Catalyst for Ethylene Dimerization Prepared by Selectively Doping Ni on the Surface of a Zeolitic Imidazolate Framework

Abstract: The production of 1-butene by ethylene dimerization is an important chemical industrial process currently implemented using homogeneous catalysts. Here, we describe a highly active heterogeneous catalyst (Ni-ZIF-8) for ethylene dimerization, which consists of isolating Ni-active sites selectively located on the crystal surface of a zeolitic imidazolate framework. Ni-ZIF-8 can be easily prepared by a simple one-pot synthesis method in which site-specific anchoring of Ni is achieved spontaneously because of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 60 publications
12
74
0
Order By: Relevance
“…Therefore, 3DOSA-ZIF-8 has not only intrinsic micropores from the molecular framework of the ZIF-8 phase but also the desired interconnected macropores between neighboring spheres and thus presents as a unique multilevel or hierarchical porous single-crystalline material. The corresponding selected area electron diffraction (SAED) pattern (Figure h) displays an ordered diffraction spot array from which we can infer that the crystal axis is along the [111] direction, reconfirming the single-crystalline nature of 3DOSA-ZIF-8 . The high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image and the corresponding elemental mapping image of 3DOSA-ZIF-8 (Figure i and j, respectively) suggest the uniform distributions of Zn, N, and C elements over the entire architecture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, 3DOSA-ZIF-8 has not only intrinsic micropores from the molecular framework of the ZIF-8 phase but also the desired interconnected macropores between neighboring spheres and thus presents as a unique multilevel or hierarchical porous single-crystalline material. The corresponding selected area electron diffraction (SAED) pattern (Figure h) displays an ordered diffraction spot array from which we can infer that the crystal axis is along the [111] direction, reconfirming the single-crystalline nature of 3DOSA-ZIF-8 . The high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image and the corresponding elemental mapping image of 3DOSA-ZIF-8 (Figure i and j, respectively) suggest the uniform distributions of Zn, N, and C elements over the entire architecture.…”
Section: Resultsmentioning
confidence: 99%
“…One nearly perfect spherical crystal selected from 3DOSC-ZIF-8 appears as a single crystal, as evidenced by the lattice-resolution TEM image (Figure S14) where consistent and continuous lattice fringes without any interfaces or domain boundaries can be clearly observed throughout the entire particle. The lattice fringes and fast Fourier transform (FFT) patterns in two different HRTEM images shot for one ZIF-8 sphere share a common crystallographic orientation, which is in good agreement with the {220} planes of ZIF-8 structure having a lattice spacing of ∼11 Å , (Figures p–r and S15). Meanwhile, the clear SAED pattern taken from a representative ZIF-8 sphere along the [111] zone axis direction further confirms the single-crystalline nature of the spheres in 3DOSC-ZIF-8 (Figure s and t), which is very consistent with the above lattice-resolution TEM results.…”
Section: Resultsmentioning
confidence: 99%
“…Electron paramagnetic resonance (EPR) spectrum of Cu‐In‐ZIF‐8 showed strong signals compared with EPR inactive ZIF‐8, implying that Cu 2+ and In 3+ might adopt a tetrahedral‐coordination geometry in the network of ZIF‐8 and thus led to unpaired electrons for the generation of EPR signals (Figure 1d). [ 10 ] Thermogravimetric analysis (TGA) demonstrated that Cu‐In‐ZIF‐8 was more prone to collapse after metal doping due to weaker coordination of Cu/In–N than Zn–N (Figure S3, Supporting Information). These results suggest that Cu and In ions are chemically bonded to the imidazolate ligand as nodes instead of being physically absorbed in the cavities of ZIF‐8.…”
Section: Resultsmentioning
confidence: 99%
“…16–18 A number of studies reported the effect of metals on the catalytic performance. Han et al 19 described that a Ni-ZIF-8 having isolating Ni-active sites located on the catalyst surface showed high activity for ethylene dimerization. Huang et al 20 investigated the structure of Ni active sites in a Ni-based catalyst for ethylene oligomerization.…”
Section: Introductionmentioning
confidence: 99%